STUDI KIMIA DAN FARMAKOLOGI TANAMAN KUNYIT (Curcuma longa L) SEBAGAI TUMBUHAN OBAT SERBAGUNA - Partomuan Simanjuntak (AGRIUM: Jurnal Ilmu Pertanian, 2012)
Abstract                Some reports indicated a great variety of pharmacological activities of kunyit, Curcuma longa  L. which exhibit anti-inflamatory, anti virus, anti bacteria, antioxidant, nematocidal activities, etc. Curcuminoids are major compounds in Curcuma longa  L responsible for the biological activity. This paper compiles an overview of those pharmacological activities and chemical compositions of the kunyit, Curcuma longa establishing its importance in health.Keywords: chemistry, pharmacology, Curcuma longa L, medicinal plants